Voluntary Activities in an Ageing Society: East and West Germany - Harald Künemund; Jürgen Schupp (Weekly Report, 2009)
SOEP respondents have been asked about their participation in voluntary activities ever since the Survey started in 1984. Here we provide evidence about stability and change in levels of participation over the last twenty years. It is often suggested that an ageing society requires, or would benefit from more voluntary and caring activity. More people are in need of assistance and there may be more people, including the retired and semi-retired, with enough time to provide it. In April 2008 Federal Minister Ursula von der Leyen (Ministry of Family Affairs, Senior Citizens, Women and Youth) announced a new initiative to foster the voluntary activities of Senior Citizens with a budget of 22 Million Euro.
Keywords: 330